Patients with IgA nephropathy have altered levels of immunomodulatory C19 steroids. Glucocorticoid therapy with addition of adrenal androgens may be the choice - Šterzl, I; Hill, M; Stárka, L; Velíková, M; Kančeva, R; Jemelková, J; Czerneková, L; Kosztyu, P; ZadraŽil, J; Matoušovic, K; Vondrák, K; Raška, M (Physiological research, 2017)
Glucocorticoid (GC) therapy is one of the methods of choices for treatment of autoimmune diseases (ADs). In addition, adrenal androgens are known as immunoprotective GC-antagonists. Adrenal steroids preferentially influence the Th1-components over the Th2 ones. We investigated steroid metabolome (using gas chromatography-mass spectrometry) in healthy controls (H), GC-untreated patients with ADs different from IgA nephropathy (U), GC-treated patients with ADs different from IgA nephropathy (T) and in patients with IgA nephropathy (IgAN), which were monitored on the beginning (N0), after one week (N1) and after one month (N2) of prednisolone therapy (60 mg of prednisolone/day/m(2) of body surface). Between-group differences were assessed by one-way ANOVA, while the changes during the therapy were evaluated by repeated measures ANOVA. The ANOVA testing was followed by Duncan's multiple comparisons. IgAN patients and patients with other ADs exhibited lack of adrenal androgens due to attenuated activity of adrenal zona reticularis (ZR). Androgen levels including their 7alpha-, 7beta-, and 16alpha-hydroxy-metabolites were further restrained by GC-therapy. Based on these results and data from the literature, we addressed the question, whether a combination of GCs with delta(5)-steroids or their more stable synthetic derivatives may be optimal for the treatment of antibodies-mediated ADs.
Keywords: Immunologic Factors; Male; Middle Aged; prednisolon; Prednisolone; Adult; dospělí; mužské pohlaví; IgA nefropatie; Glucocorticoids; Androgens; lidé; glukokortikoidy; ženské pohlaví; Adrenal Glands; androgeny; Humans; Peptides; nadledviny; peptidy; imunologické faktory; Female; lidé středního věku; Glomerulonephritis, IGA